Convergence of Multiple Stimuli to a Single Gate in TREK1 and TRAAK Potassium Channels - Choveau, Frank S; Ben Soussia, Ismail; Bichet, Delphine; Franck, Chatelain C.; Feliciangeli, Sylvain; Lesage, Florian (Frontiers in Pharmacology, 2021)
Inhibitory potassium channels of the TREK1/TRAAK family are integrators of multiple stimuli, including temperature, membrane stretch, polyunsaturated fatty acids and pH. How these signals affect the gating of these channels is the subject of intense research. We have previously identified a cytoplasmic domain, pCt, which plays a major role in controlling channel activity. Here, we use pharmacology to show that the effects of pCt, arachidonic acid, and extracellular pH converge to the same gate within the channel. Using a state-dependent inhibitor, fluoxetine, as well as natural and synthetic openers, we provide further evidence that the “up” and “down” conformations identified by crystallography do not correspond to open and closed states of these channels.